Peran Sosialisasi dan Implementasi Kebijakan Pajak dalam Meningkatkan Kepatuhan Wajib Pajak di Kecamatan Setiabudi, Jakarta Selatan - Prakoso, Aryo Bimo; Ardieansyah, Ardieansyah (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to examine the role of tax policy socialization and implementation in improving taxpayer compliance in Setiabudi District, South Jakarta. As a strategic area with high economic activity, Setiabudi holds significant potential for local tax revenues, particularly from Urban and Rural Land and Building Tax (PBB-P2) and advertising tax. However, taxpayer compliance remains a challenge due to limited public understanding, lack of accessible information, and negative perceptions about taxation. This research adopts a qualitative approach using a case study method. Data were collected through in-depth interviews, field observations, and analysis of official documents such as the 2025 Budget Implementation Document (DPA-SKPD) and relevant governor regulations. The findings reveal that the tax office (UP3D Setiabudi) conducts collaborative and consistent socialization programs involving community leaders, neighborhood associations (RT/RW), and social media platforms, which positively influence public awareness and compliance. Tax incentive policies for early payments, as outlined in Governor Regulation No. 281 of 2025, were also found to be effective in boosting revenue realization. Despite challenges such as low tax literacy and limited human resources, innovations including tax consultation booths, mobile services for the elderly, and the use of digital technology offer practical solutions. The study recommends strengthening digital strategies and engaging local communities to build a more inclusive and sustainable local taxation system.